SELF-STABILIZING STRUCTURAL DESIGN OF SEMI-SUBMERSIBLE UNMANNED BOAT - LI Wei; LU XingYi; WU Di; HU QingSong; ZHANG LiZhen (Jixie qiangdu)
The design of the self-stabilizing structure is the key to the design and research of semi-submersible unmanned boat,which directly affects the self-stabilization state of the boat in the water. By calculating and adjusting the center of gravity and buoyancy of the structure of the boat,it can sail stably in large wind waves and water currents. The structure of the boat adopts the modular idea design method. By changing the weight and volume of the module,the center of gravity and the floating center of the whole structure are more easily adjusted; based on the theoretical calculation of the center of gravity and the floating center,the arrangement and installation between the hull modules can be adjusted. In addition,the initial stability of the boat was analyzed and a Matlab program was calculated. The verification of the calculation results shows that the design of the selfstabilizing structure of the boat meets the requirements. The lake test and the sea test prove that the boat can effectively resist the wind and water flow interference,and verify that the overall self-stable structure design of the boat is reasonable and effective. At the same time,the research results can also provide some reference for the design of the semi-submersible unmanned boat.